Allenols versus Allenones: Rhodium‐Catalyzed Regiodivergent and Tunable Allene Reactivity with Triazoles. Issue 55 (4th September 2017) - Alcaide, Benito; Almendros, Pedro; Cembellín, Sara; Martínez del Campo, Teresa; Palop, Guillermo
Abstract: 2‐Pyrrolines and 6‐oxo‐hexa‐2, 4‐dienals have been prepared through the divergent reactions of 1‐benzenesulfonyl‐4‐aryl‐1, 2, 3‐triazoles with functionalized allenes. The rhodium‐catalyzed reactions between allenols and 1‐benzenesulfonyl‐4‐aryl‐1, 2, 3‐triazoles yielded 2‐pyrrolines. This transformation is compatible with the presence of aliphatic, aromatic, heterocyclic, amide, and halogen functional groups. Interestingly, a reactivity switch took place when the allene‐tethered alcohol substrate was replaced by its ketone counterpart. When the rhodium‐catalyzed reaction of 1‐benzenesulfonyl‐4‐phenyl‐1, 2, 3‐triazole was performed with allenones, acyclic 6‐oxo‐hexa‐2, 4‐dienals were stereoselectively formed as (2 Z, 4 E ) isomers. Abstract : All against all : The rhodium‐catalyzed reaction of 1‐benzenesulfonyl‐4‐aryl‐1, 2, 3‐triazoles with functionalized allenes, namely allenols and allenones, has selectively afforded in a divergent way, 2‐pyrrolines and 6‐oxo‐hexa‐2, 4‐dienals.